TRAINING THE ANALYSIS SKILLS OF STUDENT THROUGH THE APPLICATION OF GUIDED INQUIRY LEARNING MODELS ON REACTION RATE MATERIALS - Fatimah Millenia Fauziah; Dian Novita (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
This study aims to describe the feasibility of learning models, student activities, learning outcomes, analytical skills, and students' responses by applying guided inquiry learning models. The research method used was one group pretest-posttest design. The results obtained were (1) the percentage of the quality of the implementation of learning for three consecutive meetings, namely 96.87%, 96.87%, and 93.75%. (2) Students activities relevant to practicing analytical skills for three successive meetings are 88.67%, 90%, and 90.67%. (3) Student learning outcomes increased with the percentage of n-gain in the high category of 94.11%. (4) Each component of the students' analytical skills was, respectively, elemental analysis of 64.71% in the high category. In comparison, the analysis of relationships and organizational principles was 47.06% in the high category. (5) The students' responses were 92.70% and 91.92% for the learning model and LKPD. Therefore, the guided inquiry learning model can train students' analytical skills.